Classifying, downgrading, reclassifying. The French "women`s" tennis ranking categories facing the test of change? - Fontaine, M.; Hidri Neys, O. (Movement & Sport Sciences - Science & Motricité, 2025)
In the vein of work carried out in the sociology of sport over the last thirty years or so on high-level sport, this article focuses on women`s tennis. Based on a quantitative survey of 5293 French female competitive players, this article invites us to distance ourselves from the the French Tennis Federation (FFT) classification categories as potential categories for sociological analysis. Our results show the limits of taking institutional rankings into account in order to understand the conditions of existence, practice and performance of female tennis players. Based on a multiple correspondence analysis followed by a hierarchical ascending classification, three typical profiles were identified: the `Sunday` players practising in the `leisure-pleasure` mode, the `eclectic` players, with heterogeneous socio-demographic characteristics, sharing the common point of moving towards a `serious leisure activity`, and finally the `vulnerable` players devoting themselves exclusively to their `profession` even though they continue not to be recognised as workers in their own right.